Efektifitas ZnO doping TiO2 Dalam Mendegradasi Zat Warna Metil Hijau dengan Metode Fotolisis - Alfarisi, Fadil; Sanjaya, Hary; Beri, Deski; Etika, Sri Benti (Departemen Kimia FMIPA UNP, 2023)
The textile industry sector in Indonesia is progressing. This progress is not followed by good and effective waste management. Methyl green dye waste is one example. Methyl green is organic waste that is difficult to decompose and is toxic. Therefore, an effective method is needed to decompose organic waste into environmentally friendly compounds using the photolysis method. This study aims to obtain the optimum time and the optimum concentration of TiO2 doping on the degradation of Methyl green by photolysis. The percentage of degradation of Methyl green was obtained from the measurement of the absorbance value using a UV-Vis spectrophotometer at the maximum wavelength of Methyl green (λmax) and the maximum wavelength was obtained at 640 nm. The results are the optimum time of degradation of Methyl green dye at radiation time of 150 minutes with a degradation percentage of 97.5%. In the variation of TiO2 dopant concentration, the optimum concentration of TiO2 dopant was found at 10% ZnO-TiO2 with 95% degradation.